Determinan Pengambilan Keputusan Struktur Modal - Putri Eka Permatasari; Kartika Hendra Ts; Bambang Mursito (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study seeks to examine how firm size, sales growth, profitability, liquidity, and bankruptcy risk influence the capital structure of property and real estate companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The sample includes 10 companies chosen through purposive sampling, adhering to criteria like consistent annual financial report publication and complete data. Observing financial data over five years yielded 50 data points for analysis. A quantitative method with a positivist approach was employed, with data collected from financial reports on the official IDX website and analyzed via multiple linear regression. The results demonstrate that factors such as company size, sales growth, profitability, and bankruptcy risk do not significantly influence capital structure, suggesting that these elements are not critical factors in decisions regarding debt financing. On the other hand, liquidity has a notable negative impact on capital structure, indicating that firms with higher liquidity are more likely to rely on internal funds, thereby decreasing their dependence on external sources of financing. This study provides insights for companies in managing capital structure and highlights the importance of liquidity as a key factor in financing decisions.